1999
DOI: 10.1016/s0304-4203(98)00068-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers as organic-carbon-source and environmental indicators in the Late Quaternary Arctic Ocean: problems and perspectives

Abstract: In order to examine the variation in marine and terrigenous sources of the organic matter during the last 15,000 Cal. yr Ž BP, hydrogen index values, CrN ratios, and specific biomolecules short-and long-chain n-alkanes, short-chain fatty acids, . sterols, alkenones, and pigments were determined in three sediment cores from the Laptev Sea continental margin. The results show that the interpretation of the biomarker data is much more complicated and less definitive in comparison to similar data sets from low-lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 66 publications
4
64
0
1
Order By: Relevance
“…The slight differences observed between these samples are in accordance with existing knowledge on diagenetic transformation of bottom sediment OM in continental shelf and deeper sediments (Degens and Mopper, 1976;Yunker et al, 1995;Fahl and Stein, 1999;Yamamoto et al, 2008;Petrova et al;.…”
Section: Polycyclic Aromatic Hydrocarbons (Pah)supporting
confidence: 90%
“…The slight differences observed between these samples are in accordance with existing knowledge on diagenetic transformation of bottom sediment OM in continental shelf and deeper sediments (Degens and Mopper, 1976;Yunker et al, 1995;Fahl and Stein, 1999;Yamamoto et al, 2008;Petrova et al;.…”
Section: Polycyclic Aromatic Hydrocarbons (Pah)supporting
confidence: 90%
“…Sterols support the terrestrial source: they had high fluxes as well as their maximum contents (not shown) in these two cups (Table 1). Whereas campesterol and X -sitosterol are derived from higher land plants (Huang and Meinschein, 1976;Volkmann, 1984), dinosterol and brassicasterol can be derived from both fresh water and marine algae (Fahl and Stein, 1999;Robinson et al, 1984;Thiel, 1993;Yunker et al, 1995). As fluxes and contents of all sterols were significantly correlated we can assume that the algal sterols were mainly fresh-water derived.…”
Section: Ice Covered Seasonmentioning
confidence: 96%
“…Brassicasterol and dinosterol have been used as phytoplankton biomarkers (see Fahl and Stein, 1999;Volkman, 1986;Volkman et al, 1993). For extraction of IP 25 and sterols, 3 g of sediment was ultrasonicated (Sonorex Super RK 510, 35 Khz, 15 min) using dichloromethane:methanol (2 : 1, v/v) as solvent.…”
Section: Bartels Et Al: Atlantic Water Advection Vs Glacier Dynammentioning
confidence: 99%